Proceedings of the workshop on Cerebellum, Basal Ganglia and Cortical Connections Unmasked in Health and Disorder held in Brno, Czech Republic, October 17th, 2013 - Bareš, Martin; Apps, Richard; Kikinis, Zora; Timmann, Dagmar; Oz, Gulin; Ashe, James J; Loft, Michaela; Koutsikou, Stella; Cerminara, Nadia; Bushara, Khalaf O; Kašpárek, Tomáš (Cerebellum (London, England), 2015)
The proceedings of the workshop synthesize the experimental, preclinical, and clinical data suggesting that the cerebellum, basal ganglia (BG), and their connections play an important role in pathophysiology of various movement disorders (like Parkinson's disease and atypical parkinsonian syndromes) or neurodevelopmental disorders (like autism). The contributions from individual distinguished speakers cover the neuroanatomical research of complex networks, neuroimaging data showing that the cerebellum and BG are connected to a wide range of other central nervous system structures involved in movement control. Especially, the cerebellum plays a more complex role in how the brain functions than previously thought.
Keywords: nervové dráhy; Motor Activity; Czech Republic; zvířata; Autistic Disorder; mozeček; lidé; mozková kůra; autistická porucha; pohybová aktivita; Česká republika; Animals; Basal Ganglia; Cerebellum; Cerebral Cortex; Humans; bazální ganglia; Neural Pathways